2017
DOI: 10.3892/etm.2017.4236
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33a promotes cell proliferation and inhibits apoptosis by targeting PPARα in human hepatocellular carcinoma

Abstract: Abstract. ) is dysregulated in a number of human cancers, where it functions as an oncogenic miRNA. However, the clinical significance of miR-33a and its underlying molecular pathways regarding the progression of hepatocellular carcinoma (HCC) are currently unknown. In the present study, it was observed that the level of miR-33a expression was significantly increased in HCC tissues, relative to adjacent non-tumor tissues. Increased miR-33a expression was significantly correlated with poor prognostic features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…It was demonstrated that miR-33a could promote cell growth by modulating the proliferation and apoptosis of HCC cells. Its direct target is PPARα, one of the targets of mTORC1[ 36 ].…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
“…It was demonstrated that miR-33a could promote cell growth by modulating the proliferation and apoptosis of HCC cells. Its direct target is PPARα, one of the targets of mTORC1[ 36 ].…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
“…RNA was extracted and prepared for qRT-PCR as previously described (13). Total RNA was reverse-transcribed to cDNA with PrimeScript Reverse Transcriptase kit (Takara, Dalian, China) according to the manufacturer's protocol.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
“…Chang et al found that miRNA-33a can promote Huh7 cell proliferation and inhibit apoptosis in vitro. The main target of this gene is PPARα (43). In addition, the Shah team found that activation of PPARα promoted HCC cell proliferation and induced hepatocarcinogenesis, and was associated with miRNA-let7C.…”
Section: Discussionmentioning
confidence: 99%